Supervisory Needs of Schools in Bongao Island - Anqui, Princess; Ibrahim, Anhar; Lajarato, Fatima Rafhayza; Murih, Fatimah Rañia (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the supervisory needs of schools in Bongao Island, Tawi-Tawi, focusing on human resource development, school head qualifications, school facilities, and technology integration. It employed a non-experimental, explanatory sequential mixed-methods research design involving school heads and teachers as respondents. Quantitative data were gathered through research instruments using a Likert scale, while qualitative data were obtained through interviews. The data were analyzed using SPSS version 25, descriptive statistics, non-parametric tests, regression analysis, the general linear model, and Cronbach’s alpha reliability testing. Findings showed high internal consistency across the four supervisory dimensions, with Cronbach’s alpha values ranging from .906 to .982. Respondents gave generally high ratings to all dimensions, with School Head Qualification receiving the highest overall mean and Technology Integration receiving the lowest, although still positive. Regression results showed that age had a negative significant relationship with Human Resource, while years of experience had a positive significant relationship. Gender significantly affected Technology Integration, and the interaction between gender and educational background was also significant. Qualitative findings revealed continuing needs in teacher support, professional development, fair supervision, leadership competence, facility maintenance, resource allocation, stakeholder collaboration, technology access, and ICT capability-building. The study concluded that supervisory needs in Bongao schools are shaped by human resource support, leadership capacity, facilities, and digital readiness. Further research was recommended to examine these relationships more deeply and identify other factors influencing supervisory perceptions. The study supports SDG 4, Quality Education; SDG 9, Industry, Innovation and Infrastructure; SDG 16, Peace, Justice, and Strong Institutions; and SDG 17, Partnerships for the Goals. Its sustainability impact lies in strengthening educational governance, institutional planning, teacher development, safe learning environments, community collaboration, and technology-supported learning in Bongao schools.
Keywords: Educational Governance; Human Resource Development; School Facilities; School Head Qualifications; School Supervision; Stakeholder Collaboration; Supervisory Needs; Technology Integration